Exploration of Geometric Patterns in Ciwaringin Batik Motifs in Primary School Mathematics Learning - Muhamad Nur Iswandi; Nailah Tresnawati; Dina Pratiwi Dwi Santi (Journal of Research and Educational Research Evaluation, 2024)
Local cultures such as batik are increasingly being undermined by globalisation. Education and culture are components that cannot be avoided in everyday life because both are basic needs for every member of society. The purpose of this study is to analyse geometric patterns in local wisdom in the form of Ciwaringin batik motifs that can be integrated into mathematics learning in elementary schools using the ethnomathematics approach. The method used in this research is descriptive qualitative method with ethnomathematics approach. The object of this study consisted of five Ciwaringin batik motifs namely Tebu sekeret, Gambir setemplik, Gribigan, Tambang manis, and Kembang jeruk. The result of this research is that the motifs in Ciwaringin batik have geometry aspects such as straight lines, curved lines, points, angles, squares, and triangles. These aspects can be used as media for HOTS-based questions that can improve the ability to think critically, creatively, analytically, and be able to solve a problem. With the combination of HOTS and ethnomathematics, not only cultural aspects are preserved, but also mathematics learning becomes more contextual and relevant to students' daily lives.